2018
DOI: 10.1002/joc.5941
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the southern Indian Ocean dipole on the impact of El Niño–Southern Oscillation on Australian summer rainfall

Abstract: This study investigates the modulation of the southern Indian Ocean dipole (SIOD) upon the impacts of the El Niño–Southern Oscillation (ENSO) on Australian summer rainfall (ASR) on an inter‐annual timescale. First the SIOD is identified as an important factor influencing rainfall anomalies over northeastern Australia via a zonal vertical circulation spanning from the southern Indian Ocean (SIO) to northern Australia. When ENSO and the SIOD are out of phase, the El Niño‐induced anticyclonic and convection anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In tropical regions with seasonally variable precipitation, flowering pulses in palms often occur according to precipitation patterns (Abrahamson, 1999). We do not know what triggers the initiation of flowering in T. spectabilis plants; however, the flowering events recorded during this study appear to coincide with the El Niño Southern Oscillation (ENSO) cycle and possibly the interaction of this and the Indian Ocean Dipole (IOD) (Fedorov & Philander, 2000; Gong et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…In tropical regions with seasonally variable precipitation, flowering pulses in palms often occur according to precipitation patterns (Abrahamson, 1999). We do not know what triggers the initiation of flowering in T. spectabilis plants; however, the flowering events recorded during this study appear to coincide with the El Niño Southern Oscillation (ENSO) cycle and possibly the interaction of this and the Indian Ocean Dipole (IOD) (Fedorov & Philander, 2000; Gong et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Trade winds cause changes in upwelling, which lead to SST variability. Regarding the in uence of the SIOD on climate, it is obvious that the SIOD has some impact on climate at low, middle, and even high latitudes (Liu et al 2019;Gong et al 2019; Udy et al 2021). Reason (2001Reason ( , 2002 showed that positive SST anomalies of a positive SIOD enhance summer precipitation in the Southern Hemisphere through water vapor convergence.…”
Section: Introductionmentioning
confidence: 99%
“…The ITCZ is in uenced by a combination of SST and the monsoon in the Indian Ocean (Jiang 1988). Gong et al (2019) analyzed the correlation between Indian Ocean ITCZ variability and the Arctic Oscillation and found that vertical air motion at the location of the ITCZ was signi cantly correlated with the Arctic Oscillation. On the other hand, Chan and Evans (2002) demonstrated that the location of the ITCZ and the monsoon are crucial in controlling ow and precipitation patterns, the development of tropical cyclones, and the hydrological cycle in the area.…”
Section: Introductionmentioning
confidence: 99%
“…There exists significantly negative correlation between the SIOD and ENSO but some SIOD cases are formed without the effect of ENSO by Indian Ocean intrinsic processes through the changes of surface latent heat flux in relation with the wind speed fluctuations (Behera and Yamagata, 2001; Zhang et al ., 2020). Both the statistical and model studies have documented the significant impacts of SIOD on the climate variability over the Indian Ocean rim and remote regions (Rai and Pandey, 2008; Cao et al ., 2014; Zhang et al ., 2017; Gong et al ., 2019). Through the modulation of the anomalous convection heating over the Maritime Continent and vapour transportation, the SIOD could influence the summer rainfall distribution in China (Yang and Ding, 2007; Cao et al ., 2014; Jin et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%